Analisis Peningkatan Customer Satisfaction Pelanggan Indihome Melalui Service Quality Dan Brand Image - Silvia Ekasari; Hendy Tannady; Erwin Gunawan; Irma M Nawangwulan; Samuel PD Anantadjaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the impact of the influence of brand image and service quality on customersatisfaction in Indihome North Jakarta area. The number of samples was 167 respondents using multiple linearregression sampling method. Using the IBM SPSS Statistics 25 program for multiple linear regression analysis. This studyuses a quantitative method through a questionnaire survey distributed from google form. The results in the study can beseen that each independent variable has a positive and significant effect on customer satisfaction in the Indihome NorthJakarta area partially. Keywords: Brand Image, Service Quality, Customer Satisfaction